The Royale Enterprise: case study: company analysis / Mohd Ishraffil Ezzrail Mohd Jusni … [et al.] - Mohd Jusni, Mohd Ishraffil Ezzrail; Zulkarnain, Nur Kiasatina Anantasha; Ahmad Khiril Azam, Muhamad Aiman Akmal; Shazman, Rose Aidatul Azita; Muhamad Jamri, Ezzat Imani (2021)
The Royale Roselle Company was established in March 2020 and as our company, we produce The Royale Roselle Tea and we came up with an idea to become a social business. For information, a plant that is renowned for its nutrients in the medicinal field of Malaysia, known as Roselle or its formal name Hibiscus Rosa sabdariffa L was originally produced for decoration only. The Royale Roselle will not stand out without our staff. As a social business, we plan to serve a single mother from Malacca Single Mother Association (MSMA) as our workers that mainly focus on product manufacturing department from starting point until finishing point. The Royale Roselle Company sets a target market based on demographic, psychographics and geographics. These target market play an important role towards business because it enhances better in marketing performance results and have an ability to provide a better and right product to the consumers. We plan to launch our first The Royale Roselle Shop in Malacca because it is the place where all the fresh roselle will be plant and produce as for now our headquarter are operated in Kuala Lumpur. During this launching day, we target about 300 people will buy our product with affordable price and 50% discount for 2nd purchases of any product with a single receipt. Our business plan consists of four plans which are Marketing Plan, Production Plan, Organization Plan and Financial Plan. We used media advertising and sales promotion to promote our product in the market. The operating plan is one of the most significant aspects to consider when starting a company. We must make certain that our company is able to meet and exceed the expectations of our clients. However, it is critical to guarantee that the company can provide the product that was envisioned in the marketing plan before proceeding with the project.